2018
DOI: 10.1073/pnas.1716713115
|View full text |Cite
|
Sign up to set email alerts
|

Transient fibrosis resolves via fibroblast inactivation in the regenerating zebrafish heart

Abstract: SignificanceAfter myocardial infarction in the mammalian heart, millions of cardiomyocytes are lost and replaced by fibrotic scar tissue. While fibrosis is persistent in adult mammals, there are some vertebrates, including zebrafish, with the capacity for regeneration. This process does not occur in the absence of fibrosis. Here we studied subpopulations of collagen-producing cells and analyzed their fate after complete regeneration of the zebrafish myocardium. Our data show that fibroblasts persisted in the r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
208
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(217 citation statements)
references
References 43 publications
8
208
0
1
Order By: Relevance
“…In addition, we found that the Runx1-Citrine positive thrombocytes that make up a large proportion of the wound express Myh11. Surprisingly, we observed most collagen deposition in the wound localised adjacent to the Myh11 expressing endocardial cells and thrombocytes, and to a much lesser extent near the epicardium, despite the fact that the epicardium is considered the main source of myofibroblasts and collagen deposition in the heart (37,40). This suggests that while these cells retain the characteristics of endocardial cells and thrombocytes, they can function analogously to myofibroblasts.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…In addition, we found that the Runx1-Citrine positive thrombocytes that make up a large proportion of the wound express Myh11. Surprisingly, we observed most collagen deposition in the wound localised adjacent to the Myh11 expressing endocardial cells and thrombocytes, and to a much lesser extent near the epicardium, despite the fact that the epicardium is considered the main source of myofibroblasts and collagen deposition in the heart (37,40). This suggests that while these cells retain the characteristics of endocardial cells and thrombocytes, they can function analogously to myofibroblasts.…”
Section: Discussionmentioning
confidence: 70%
“…Absence of these cells could, therefore, explain the different wound composition as well as the enhanced regeneration in the runx1 mutant. This is a novel and surprising finding, as the epicardium is considered the main source of myofibroblasts and collagen deposition in the heart (37,39,40).…”
Section: Smooth Muscle Genes Are Expressed In the Endocardium And Thrmentioning
confidence: 91%
See 2 more Smart Citations
“…These include maturation of cardiac fibroblasts, activity of macrophages and other immune cells, ECM composition and rigidity, as well as physiological hypoxia and hormonal regulation. 14,28,41,42 Investigating the discordance in timing of cardiac maturation and regenerative capacity in pigs could be useful to define relative contributions of multiple cell types and physiological factors in heart regeneration. Here, we show that ECM remodeling is significant by P7 in pigs, contributing to increased rigidity of the matrix, while maturational collagen remodeling continues to 6mo.…”
Section: What Dictates Postnatal Regenerative Capacity Of the Mammalimentioning
confidence: 99%